CX3CR1 at V249M and T280M Gene Polymorphism and Its Potential Risk for End-Stage Renal Diseases in Egyptian Patients - Asmaa Fathelbab Ibrahim; Asmaa Osama Bakr Seddik Osman; Lamiaa M. Elabbasy; Mostafa Abdelsalam; A. M. Wahab; Maysaa El Sayed Zaki; Radwa Ahmed Rabea Abdel-Latif (International Journal of Nephrology)
CX3CL1-CX3CR1 pathway may be one of the future treatment targets to delay the progression of end-stage renal diseases. This study aimed to evaluate the CX3CR gene polymorphism in Egyptian patients with ESRD and its relation to fractalkine blood level. The study included 100 patients with ESRD on dialysis, 61 males and 39 females with mean age 51.02 ± 7.8 years. The V2491 genotype revealed a significant increase in the frequency of GG genotype in healthy control (83%) compared to patients [69%] with a significant increase in GA in patients [30%] compared to control subjects [15%], P = 0.03. T280M study showed a statistically significant prevalence of TT genotype in healthy control subjects [86%-OR 95% CI 1.7] compared to patients [70%] with a significant increase in the prevalence of TA in patients [29%] compared to control subjects [13%], P = 0.01. There was a significant increase in fractalkine levels in genotypes GA + AA [503.04±224.1] pg/ml compared to genotype GG [423.6 210.3], P = 0.03. Moreover, there was a significant increase in the blood level of fractalkine in genotype TA + AA [498.8 219.6] compared to genotype TT [426.8±212.8], P = 0.05. In conclusion, our study showed that both V2491-GA genotype and T280M-TA are associated with potential risk for end-stage renal disease in Egyptian patients.